CC.OO. (“Comisiones Obreras”) – ISTAS (Union Institute of Work, Environment and Health) participatory action plan for a healthier work organization: A case study - Moncada, Salvador; Llorens, Clara; Moreno, Neus; Rodrigo, Fernando; Landsbergis, Paul (Safety science, 2011)
Spanish workers have been among the most exposed to psychosocial risks across the European Union. CC.OO. and ISTAS decided to establish an action plan to empower workers’ health and safety representatives to have an influence on the psychosocial risk assessment processes leading to negotiations with employers over a more democratic, fair and healthier work organization. Most important outcomes included 3600 companies which have followed a participatory process culminating with the implementation of agreed upon at source preventive measures in 40% of cases. There exists some evidence that preventive actions have increased in Spain since CC.OO.’s workers’ health and safety representatives started systematically pushing for improvements in the psychosocial work environment, however the quality of such actions is less clear. Future priorities include: first, to overcome barriers related to the interaction with external agents, especially with professional and administrative bodies. Second, to increase collaboration with scientific institutions to ensure and improve quality of both risk assessment tools and preventive actions. Third, to evaluate at the source interventions at company level with special interest in looking at the involvement of worker representatives, managers and OH professionals and the impact of their involvement on the undertaking of effective preventive actions. Fourth, increasing interaction between ISTAS and CC.OO. in order to place demands for the improvement of psychosocial working conditions more centrally in collective bargaining. Fifth, trying to increase unity of action of all Spanish workers’ unions on the subject.